The Impact of Environmental Policy on Innovation in Clean Technologies - Eugster, Johannes (IMF Working Papers; Working Paper ;, 2021)
This paper studies the effect of climate change mitigating policies on innovation in clean energy technologies. Results suggest that the tightening of environmental policies since the early 1990s have made a statistically and economically significant contribution to the increase in clean innovation. These effects generally materialized quickly, within 2 to 3 years of the policy change, and were driven by individually significant marginal effects of both market-based policies - such as feed-in tariffs and trading schemes - as well as non-market policies, such as R and D subsidies or emission limits. Looking at electricity innovation in particular, the paper finds that the estimated effect on total innovation is positive on net, meaning that increased innovation in clean and grey technologies is not offset by a decrease in innovation in dirty technologies. From a policy point of view, the paper's results call for strong policy efforts to decisively shift innovation towards clean technologies.